PRODUKSI BIOETANOL BERBASIS SINGKONG DAN TEBU DI INDONESIA: REVIEW LITERATUR DAN ANALISIS KEBERLANJUTAN - Febryansyah, Azmy; Warohmah, Cicah; Zahratunnisa, Alya Rahma (Biospecies, 2026)
Bioethanol is a promising renewable energy source that can reduce dependence on fossil fuels while supporting sustainable development. In Indonesia, cassava and sugarcane, including their agricultural residues, have significant potential as bioethanol feedstocks due to their abundant availability and high carbohydrate content. This study aimed to synthesize the development of bioethanol production technologies based on cassava and sugarcane in Indonesia and to evaluate their sustainability from environmental, economic, and social perspectives. A literature review was conducted using scientific publications retrieved from Google Scholar, ScienceDirect, and ResearchGate published between 2015 – 2025. Following a systematic selection process based on predefined inclusion and exclusion criteria, 15 articles were selected and analyzed using a narrative synthesis approach. The results indicate that Saccharomyces cerevisiae is the most widely used microorganism for fermentation, while bioethanol yield is strongly influenced by feedstock characteristics, pretreatment methods, hydrolysis techniques, and fermentation conditions. From a sustainability perspective, utilizing agricultural residues such as sugarcane bagasse and cassava waste contributes to reducing agro-industrial waste, lowering carbon emissions, increasing economic value, and supporting national energy security. However, most studies remain limited to laboratory-scale experiments and rarely incorporate Life Cycle Assessment (LCA) or Techno-Economic Assessment (TEA). Future studies should focus on pilot- and industrial-scale implementation while integrating comprehensive sustainability assessments to support large-scale bioethanol development in Indonesia.